2006
DOI: 10.1063/1.2162541
|View full text |Cite
|
Sign up to set email alerts
|

Formal relations connecting different approaches to calculate relativistic effects on molecular magnetic properties

Abstract: Articles you may be interested in A fully relativistic method for calculation of nuclear magnetic shielding tensors with a restricted magnetically balanced basis in the framework of the matrix Dirac-Kohn-Sham equationa) J. Chem. Phys. 128, 104101 (2008) In the present work a set of formal relations connecting different approaches to calculate relativistic effects on magnetic molecular properties are proven. The linear response ͑LR͒ within the elimination of the small component ͑ESC͒, Breit Pauli, and minimal-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Visscher suspects that missing positive-energy-negative-energy orbital rotations or the standard restricted kinetic-balance for negative-energy states might produce the differences [59]. In contrast to Visscher's pilot study, similar results were found by Zaccari et al [60] for the linear response within the elimination of the small component framework and Kutzelnigg's approach. In recent work, Xiao and co-workers have addressed the proper and efficient implementation of magneticfield like properties [35].…”
Section: Introductionsupporting
confidence: 55%
“…Visscher suspects that missing positive-energy-negative-energy orbital rotations or the standard restricted kinetic-balance for negative-energy states might produce the differences [59]. In contrast to Visscher's pilot study, similar results were found by Zaccari et al [60] for the linear response within the elimination of the small component framework and Kutzelnigg's approach. In recent work, Xiao and co-workers have addressed the proper and efficient implementation of magneticfield like properties [35].…”
Section: Introductionsupporting
confidence: 55%
“…Zaccari and coworkers published the formal relation that relate the BBPT (Breit–Pauli perturbation theory) approach and another one formulated by Kutzelnigg . These three proposals appeared almost at the same time and started from different grounds.…”
Section: Models and Levels Of Approachmentioning
confidence: 99%
“…To assess the completeness of LRESC regarding its theoretical grounds, in Ref. , Zaccari et al focused on the formal relations that shows the gauge invariance of the LRESC method, and compared this scheme with two other similar descriptions for shielding constants, namely the Breit–Pauli approximation presented by Vaara and coworkers and the approach proposed by Kutzelnigg in Ref. .…”
Section: Applications Of the Lresc Modelmentioning
confidence: 99%
“…The equivalence of the total result of the usual Breit-Pauli and LRESC schemes was theoretically proven, although the particular operators involved are different. 37 The LRESC or Breit-Pauli schemes are interesting because they present several advantages compared to other approaches. First, from the physical point of view, they are based on the Schrödinger Hamiltonian and perturbation operators are amenable to physical interpretation in terms of usual nonrelativistic spin orbitals.…”
Section: Relativistic Two-component Geometric Approximation Of the Elmentioning
confidence: 99%